2007
DOI: 10.1021/ol0705752
|View full text |Cite
|
Sign up to set email alerts
|

2-Alkenoyl Pyridine N-Oxides, Highly Efficient Dienophiles for the Enantioselective Cu(II)−Bis(oxazoline) Catalyzed Diels−Alder Reaction

Abstract: 2-Alkenoyl pyridine N-oxides are introduced as a new kind of efficient dienophiles for the Cu(II)-bis(oxazoline) (BOX) catalyzed enantioselective Diels-Alder reaction affording higher reactivity and enantioselectivity (ee's up to 96%) than the corresponding nonoxidized 2-alkenoyl pyridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…These results compare favorably with those obtained using a homogeneous metal catalyst 41 or in the presence of various hybrid catalysts taking advantage of proteins, 42,43 or DNA 44,45 to induce stereoselectivity.…”
Section: Diels-alder Cycloadditionsupporting
confidence: 63%
“…These results compare favorably with those obtained using a homogeneous metal catalyst 41 or in the presence of various hybrid catalysts taking advantage of proteins, 42,43 or DNA 44,45 to induce stereoselectivity.…”
Section: Diels-alder Cycloadditionsupporting
confidence: 63%
“…[12] 2-Alkenoylpyridines 2 (Scheme 2) have been used as dienophiles in catalytic enantioselective DA reactions with a number of catalysts. [13] However, in a previous work, [14] we found that these substrates failed to give the DA reaction in the presence of the "privileged" BOX-Cu(II) complexes (Figure 1). [15] This problem could be overcome by using the related 2-alkenoylpyridine N-oxides 3 as dienophiles.…”
mentioning
confidence: 85%
“…They have been used to control the chirality in asymmetric synthesis, and they have also been found to act as inhibitors of human severe acute respiratory syndrome (SARS), human immunodeficiency virus (HIV), and feline infectious peritonitis corona virus 2‐Acylpyridine N ‐oxides are used as prochiral ketones in the asymmetric Henry reaction to give tertiary nitro aldols, which are building blocks for the synthesis of pharmaceuticals and agrochemicals (Figure , compound A ). They show excellent chelating properties in several asymmetric metal‐catalysed reactions, and they have also been used as precursors for the synthesis of norbormide (NRB; Figure , compound B ), which acts as a rat‐selective toxicant, vasoconstrictor, and calcium‐channel blocker …”
Section: Introductionmentioning
confidence: 99%